FREE Registration for online tutoring and homework help.

Need to get the answer to this problem by using elimination: =x-3y=61 and 2x+y=-7

Friday, July 23rd, 2010


  1. 2x –  =y=61
  2. 2x +   y= =7

If you subtract the second equation from the first, you can eliminate x and you are left with -4y = 68.

So y = 3D -17, and plugging this into the first equation we can figure out

y:  2x = (-51)=61,

so x = 5

This entry was posted on Friday, July 23rd, 2010 at 9:24 am and is filed under 9th Grade, Homework Answers, Math Answers. You can follow any responses to this entry through the RSS 2.0 feed. You can leave a response, or trackback from your own site.

Leave a Reply